2006
DOI: 10.1211/jpp.58.7.0015
|View full text |Cite
|
Sign up to set email alerts
|

Relevant activities of extracts and constituents of animals used in traditional Chinese medicine for central nervous system effects associated with Alzheimer's disease

Abstract: The centipede Scolopendra subspinipes mutilans L. Koch ('Wugong'), the beetle Mylabris phalerata Pallas ('Ban mao') and the earthworm Pheretima aspergillum Chen ('DiLong') have a reputation in traditional Chinese medicine for reducing symptoms of central nervous system decline, including memory loss. A series of extracts of all three organisms was tested for acetylcholinesterase (AChE) inhibition and copper ion binding effects, the latter likely to reduce oxidative damage caused by excess copper. The beetle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…AChE activity was measured using a 96-well microplate reader (Ren et al, 2006;Mukherjee et al, 2007b) based on Ellman's method (Ellman et al, 1961). The enzyme hydrolyses the substrate acetylthiocholine resulting in the product thiocholine which reacts with Ellman's reagent (DTNB) to produce 2-nitrobenzoate-5-mercaptothiocholine and 5-thio-2-nitrobenzoate which can be detected at 405 nm.…”
Section: Chemicals Acetylthiocholine Iodide (Atci) Acetylcholinestementioning
confidence: 99%
“…AChE activity was measured using a 96-well microplate reader (Ren et al, 2006;Mukherjee et al, 2007b) based on Ellman's method (Ellman et al, 1961). The enzyme hydrolyses the substrate acetylthiocholine resulting in the product thiocholine which reacts with Ellman's reagent (DTNB) to produce 2-nitrobenzoate-5-mercaptothiocholine and 5-thio-2-nitrobenzoate which can be detected at 405 nm.…”
Section: Chemicals Acetylthiocholine Iodide (Atci) Acetylcholinestementioning
confidence: 99%
“…In an effort to evaluate the bioactive potential of the leaf extract of Cynometra couliflora L., in different solvents using Ellman's calorimetric method in a 96 well plate, Ado, Abas [61] demonstrated that although ethyl acetate fraction exhibit better potency against AChE. Generally, extracts from the more polar fractions of methanol, ethyl acetate, n-butanol and aqueous soluble fractions showed a remarkable anti AChE activity as against the corresponding hexane and dichloromethane fractions, with IC 50 values of 0.065 ± 0.008, 0031 ± 0.012, 0.11 ± 0.005 and 0.052 ± 0.015 mg/ml respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[159] reported that PUFAs have a relatively moderate effect on AChE, DHA being the strongest inhibitor. The authors suggested that long-chain PUFAs possess specific molecular features responsible for this promising activity [159]. Andrade et al .…”
Section: Neuroprotective Compounds From Macroalgaementioning
confidence: 99%